Cohesion challenges in a multicultural team : a descriptive qualitative study in a Cardiac Centre of a designated hospital in Saudi Arabia - Van Wyk, Neltjie C. (University of Pretoria, 2025)
Dissertation (MNur (Nursing Management))--University of Pretoria, 2024.